(untitled) (Journal of Forest and Livelihood, 2023)
Various forest products such as nuts, mangoes, bananas, lime, silk from mulberry leaves,essential oil, timber, animal food, perfume from tree blossoms, mulch and biochar, possess high potential to increase rural income. However, farming families in Nepal can hardly afford the investment to create such productive ecosystems. Connecting to the global market through Carbon dioxide (CO2)– certificates could serve to finance the creation of forest gardens. To test and demonstrate such approach, a project on ‘building village economies through climate farming and forest gardening (BeChange)’ has been implemented by 276 farming families in four districts (Tanhun, Lamjung, Gorkha and Kaski) of Nepal. Using Global Positioning System (GPS) point survey, household surveys, focus group discussions (FGDs), a triad group system, field observation and reports, the success of establishing privately owned forest gardens was assessed. A total of 42,205 mixed tree species such as Michelia, Elaeocarpus, and Cinnamomum tamala were planted on abandoned agriculture land of 276 families. The set-up and maintenance of the forest gardens was financed with advanced payments for the carbon sink services of the planted trees. Farmers who succeeded with tree survival rates above 70 per cent received an additional yearly carbon sink fee. This activity was linked to other income generating activities such as cultural eco-tourism, cinnamon leaf essential oil distillation, and intercropping of high value shade loving crops such as ginger, turmeric, and lentils. The outcomes of the project show significant improvements of the livelihood and food security in the project villages.